Percepción del riesgo por consumo de sustancias Psicoactivas en estudiantes universitarios en Ibagué, Colombia (2023)
We can assume risk of perception is one of the main reasons that influence the consumption of psychoactive substances, however it is important to know, which are those specific factors that are promoting and helping to increase levels of consumption in young populations, creating in fact, a health and public problem. Those factors can be identified through the study of population environment, beliefs, and psychosocial development; it is relevant to make a clear and updated perspective about what in fact is the argument about this conduct of consumption because it is crucial to create an accurate prevention and promotion program.